FAMILY EDUCATION; STRENGTH AMID THE DANGER OF INTOLERANCE - Adkha Bukhori, Ahmad Munirul Hakim, (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: Conflicts between religions that lead to violence. The clashes between religious communities in Indonesia cannot go away and happen continuously. Family indifference is also a problem for building religious tolerance. This study aims to describe family education as a major force in overcoming the threat of intolerance and its implications. This research uses qualitative research methods. Data collection was carried out through interviews, documentation, literature study and online. For in-depth interviews, the informants consisted of seven people, namely academics, community organization leaders, Islamic studies researchers, and students. The data analysis technique used descriptive analysis, data presentation and drawing conclusions. The results showed that educational activities initiated by parents in the family need to be continuously encouraged to develop the importance of the spirit of unity. Parents can provide education about noble and positive values in social life. The danger of intolerance that increasingly threatens the integration of the nation, thus family education becomes a capital of strength in countering these worries. Overall family education has an important value in teaching children to have open insights in the midst of multicultural differences in society, religion and nationality. Abstrak: Konflik antar agama yang berujung pada kekerasan. Benturan antar umat beragama di Indonesia tersebut tidak bisa hilang dan terjadi terus menerus. Sikap acuh tak acuh keluarga juga menjadi masalah untuk membangun sikap toleransi agama. Penelitian ini bertujuan untuk mendeskripsikan pendidikan keluarga sebagai kekuatan besar dalam mengatasi ancaman bahaya intoleransi beserta implikasinya. Penelitian menggunakan metode pustaka dan daring. Untuk wawancara mendalam, informan terdiri dari tujuh orang, yaitu akademisi, tokoh organisasi masyarakat, peneliti studi Islam, dan mahasiswa. Teknik analisis data menggunakan analisis deskriptif, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan, kegiatan edukatif yang diprakarsai oleh orang tua di dalam keluarga perlu terus-menerus digalakkan untuk mnegmbangkan pentingnya spirit persatuan. Orangtua dapat memberikan pendidikan tentang nilai-nilai luhur dan positif dalam kehidupan bermasyarakat. Bahaya Intoleransi yang semakin mengancam integrasi bangsa, maka pendidikan keluarga menjadi modal kekuatan dalam menangkal kekhawatiran tersebut. Secara keseluruhan pendidikan keluarga memiliki nilai penting untuk mengajarkan anak agar mempunyai wawasan yang terbuka di tengah perbedaan multikultural bermasyarakat, beragama dan berbangsa. Kata Kunci: Pendidikan Keluarga, Toleransi Beragama, Intoleransi.